2010
DOI: 10.1080/14786419.2010.497147
|View full text |Cite
|
Sign up to set email alerts
|

A validated HPTLC method for determination oftrans-caryophyllene from polyherbal formulations

Abstract: Formulations of traditional medicines are usually made up of a complex mixture of herbs. However, effective quality control methods in order to select materials of the right quality are lacking. 'Amukkara choornam' is a polyherbal Siddha formulation used for gastritis, spleen enlargement, leucorrhoea, hiccups, anaemia, tuberculosis and kappa diseases. Trans-caryophyllene is an important constituent present in the ingredients of this formulation. In a literature survey, it was found that there is no such method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Menthol was estimated using paper chromatography after treated with p-aminobenzaldehyde to produce xanthate derivative with red color (12). A validated highperformance thin layer chromatography (HPTLC) method was developed to estimate eucalyptol in a polyherbal formulation known as 'Amukkara choornam' (13). Many marketed formulations contain menthol and euclyptol among other ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Menthol was estimated using paper chromatography after treated with p-aminobenzaldehyde to produce xanthate derivative with red color (12). A validated highperformance thin layer chromatography (HPTLC) method was developed to estimate eucalyptol in a polyherbal formulation known as 'Amukkara choornam' (13). Many marketed formulations contain menthol and euclyptol among other ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…BCP improved systemic inflammation and oxidative status with no hepatotoxicity, as with nonsteroidal anti-inflammatory drugs (Ames-Sibin et al, 2018). It also reduced nausea, epigastric pain, and diarrhea, and improved gastrointestinal activity (Patra et al, 2010). BCP was also found to promote wound healing by modulating numerous signaling pathways (Parisotto-Peterle et al, 2020).…”
Section: Tissue Protective Effects Of Bcp May Be Prospective In Covid-19 Associated Organ Injuriesmentioning
confidence: 99%
“…Many formulations containing BCP have been developed, including Amukkara Choornam (Patra et al, 2010), CIN-102, a coated pellets and matrix mini-tablet (Nieto-Bobadilla et al, 2015), and PipeNig ® -FL, a high standardized content of BCP (Geddo et al, 2019). BCP is highly lipophilic, less soluble in water and, upon exposure to air, it easily oxidizes.…”
Section: Dosage Forms and Pharmaceutical Development Of Bcpmentioning
confidence: 99%
“…Several BCP-containing formulations have been developed, including Amukkara Choornam [ 133 ], CIN-102 [ 134 ], and PipeNig ® -FL [ 135 ]. In particular, a 2022 clinical trial involving 30 patients revealed that Amukkara Chooranam, a polyherbal formulation containing BCP, was able to significantly improve clinical assessment parameters in children with autism spectrum disorder [ 136 ].…”
Section: Bcp As a Functional Cb2r Agonist To Target Neuropsychiatric ...mentioning
confidence: 99%